Revolutionary grammar learning via GLOw@CBI (grammar learning online with concept based instruction) / Haliza Harun ... [et al.] - Harun, Haliza; Ab. Wahab, Nursyuhada'; Abdullah, Norhana; Zainuddin, Nurkhamimi (Universiti Teknologi MARA, 2018)
A great deal of discussion centers on finding the effective solutions to enhance language learners' competency and English language-skills to achieve the target communicative competence. While grammar instruction is regarded as crucial in acquiring the target English language, many of its' learners are still found to have poor grasps in the language. Subsequently, GLOw@CBI may offer a revolutinised approach to the teaching and learning of English grammar rules (i.e. tenses). The theoretical foundation of GLOw@CBI is based on consolidating the theory of cognitive grammar model (Radden and Dirven 2007) and Vygotsky's Systemic-Theoretical Instruction (STI) (1978) to create online lessons and exercises on grammar tenses that are easy to understand and meaningful to serve the learners' communicative purposes. The distinctive feature of GLOw@CBI is the emphasis given on the semantic aspect of the language, rather than only focusing on its' structure and function as reflected in many of the traditional grammar approaches. Thus, the strength of GLOw@CBI lies in the representation of the concept of tenses that are uniquely presented through the manipulation of 'viewing frames' to describe the target actions, situations and events. GLOw@CBI not only allows flexibility in online language learning, but it is also cost-effective, due to its' ability to enroll a large number of learners without any restrictions of users per-licensing. Moreover, due to its' unique presentation of grammar-rules, GLOW@CBI has the potential to be expanded to other grammar components in its' learning platform or even to be used to teach grammar of other foreign language courses.